Consolidation under the Europe's New Fiscal Rules: Analyzing the Implied Minimum Fiscal Effort - Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2014)
The new EU fiscal framework builds on several overlapping target measures and convergence rules. Thus, it is not clear how strict goals the framework sets for public finances. In this paper we build a simulation framework that solves the minimum fiscal effort under different assumptions on the initial state of the economy and the expected economic conditions during the consolidation. We then use the model to analyze several fiscal consolidations. We find that Germany, France, Spain and Italy are currently in compliance with our measure of minimum fiscal effort, but Spain is at risk of falling behind the required pace of consolidation in the near future. As a historical reference we revisit the Finnish Great Depression of the early 1990s. We find that the consolidation was in compliance with the fiscal rules, but during the first years of the consolidation the difficulty of detecting the phase of the business cycle could have considerably increased the restrictiveness of the rules. Finally, we address the looming sustainability gap in the Finnish public finances that reflects the cost of aging population. Under no policy change the required correction is found to become substantial by 2030.
Keywords: E61; E62; H6; 330